Killer cell immunoglobulin–like receptor 3DL1 variation modifies HLA-B*57 protection against HIV-1 - Martin, Maureen P.; Naranbhai, Vivek; Shea, Patrick R.; Qi, Ying; Ramsuran, Veron; Vince, Nicolas; Gao, Xiaojiang; Thomas, Rasmi; Brumme, Zabrina L.; Carlson, Jonathan M.; Wolinsky, Steven M.; Goedert, James J.; et al. (Journal of Clinical Investigation, 2018)
HLA-B*57 control of HIV involves enhanced CD8+ T cell responses against infected cells, but extensive heterogeneity exists in the level of HIV control among B*57+ individuals. Using whole-genome sequencing of untreated B*57+ HIV-1–infected controllers and noncontrollers, we identified a single variant (rs643347A/G) encoding an isoleucine-tovaline substitution at position 47 (I47V) of the inhibitory killer cell immunoglobulin-like receptor KIR3DL1 as the only significant modifier of B*57 protection. The association was replicated in an independent cohort and across multiple outcomes. The modifying effect of I47V was confined to B*57:01 and was not observed for the closely related B*57:03. Positions 2, 47, and 54 tracked one another nearly perfectly, and 2 KIR3DL1 allotypes differing only at these 3 positions showed significant differences in binding B*57:01 tetramers, whereas the protective allotype showed lower binding. Thus, variation in an immune NK cell receptor that binds B*57:01 modifies its protection. These data highlight the exquisite specificity of KIR-HLA interactions in human health and disease.